Analisa Yuridis Permohonan Pailit Atas Ketidakmampuan Pemenuhan Prestasi Perusahaan Yang Mengalami Force Majeure - Ulim Tjiatawi (Universitas Islam Sumatera Utara, 2022)
The bankruptcy petition filed by the creditor against the debtor who fails to perform the performance in force majeure conditions where the failure to implement the performance in a timely manner is considered as a debt that is due and billable by the creditor and the debtor who is petitioned for bankruptcy reasoned that the failure was caused by the force majeure conditions, as well as to find out the limits of the scope of force majeure, the proof of the inability to fulfill the achievements so that they are categorized as a debt that is due and billable, and the basis for the legal considerations in the cancellation of bankruptcy petitions submitted by the creditors.This research uses normative juridical research, and the nature of the research is descriptive-analytical, and legislative research approach.The absence of laws and regulations that comprehensively regulate the force majeure conditions lead to different interpretations. In considering the decision of the Commercial Court Number 53/Pailit/2012/PN.Niaga.JKT.PST and the verdict of the Supreme Court 835 K/Pdt.Sus/2012, it was decided that the demonstration was a force majeure that could not be predicted by the debtor. The force majeure condition as argued by the debtor does not include simple evidence as specified as one of the requirements in filing a bankruptcy petition, where the force majeure must be proven in a district court. The deelay in the implementation of the performance by the debtor cannot be categorized as a debt that is due and billable, because in the presence of the force majeure, the debtor is temporarily relieved of his obligations until the force majeure ends. However, the dissenting opinion of one of the member of the Supreme Court stated otherwise, that the demonstration could have been predicted by the debtor, so it could not be categorized as the force majeure, and therefore, the debtor had defaulted so that it was categorized as a debt that was due and collectible.Keywords : Force Majeure, Dissenting Opinion, Due and Billable